ANALISIS YURIDIS PENGELOLAAN DANA DESA DI TENGAH PANDEMI COVID 19 BERDASARKAN PERATURAN MENTERI DESA NOMOR 13 TAHUN 2020 TENTANG PRIORITAS PENGGUNAAN DANA DESA TAHUN 2021 - Darmawan Wiridin; Nasrin Nasrin; Sitti Aisyah; Achmad Ramli (Jurnal Ilmu Hukum Kanturuna Wolio, 2022)
The formulation of the problem on this study is how are the efforts of the Lakapera village government in managing village funs in the midts of the covid 19 Pandemic based on the village minister regulation number 13 of 2020 regarding priority of using village funds in 2021. How are the obstacles of the Lakapera Village government in managing village funds in the future covid 19 pandemic. This is study aims to identify and explain the efforts of the Lakapera Village government in conduction an analysis of the village fund management in the midst of the covid 19 Pandemic. The research method in this research is deskriptif analytic which aims tp create a picture or provide information systematically and accurately based on existing facts. Based on the result of research, the management og the village funds in the midst of the covid 19 pandemic is a challenge for the Lakapera Village government, this is because the APBDes must be allocated for handling the Covid 19 Pandemic without having to forget about development in the Village.